STRATEGI PENGEMBANGAN USAHATANI JAGUNG DI DESA TORAGET KECAMATAN LANGOWAN UTARA KABUPATEN MINAHASA (Corn Business Development Strategy in Toraget Village, North Langowan Sub District, Minahasa Regency) - Jovi Schwardz Kanter; Lyndon R. J. Pangemanan; Jane S. Tambas (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
The objective of this research is to examine the corn farming development strategy in Toraget Village, Langowan Utara Sub District, Minahasa Regency. The data used in this study are primary data and secondary data. The sampling technique in this study was by purposive sampling technique. The number of samples of farmers is 10 respondents, and stakeholders in the village of Toraget are 3 people consisting of the Toraget village government and also supervisors as development strategy experts. This study used questionnaires and interviews as well as FGDs to see how the corn farming business in Toraget Village was developed. The data analysis method used is SWOT analysis. The results of the analysis on the SWOT matrix obtained the coordinates (0.97 : 1.46) which show that these coordinates are in quadrant 1, which supports an aggressive strategy. That of all the strengths of the availability of dry land that is still wide has a weight value of 0.15 and a rating of 4, experience in corn farming has a weight value of 0.15 and a rating of 4, the existence of institutions (farmer groups and Gapoktan) has a weight of 0.12 and a rating of 3 .3, the availability of agricultural production inputs has a weight of 0.14 and a rating of 3.8. So that from all the existing strengths the corn farming development strategy in Toraget Village has the strength to be developed.